INVISIBLE SOUNDS FOR CALVINO’S INVISIBLE CITIES: COLLABORATION IN A CREATIVE PROCESS (Orfeu, 2020)
Inspired by Italo Calvino's novel Le città invisibili (1972), which presents Marco Polo's description of several invisible and fictional cities, the authors embarked on an imaginary journey to create invisible sounds with the subtlety of the fortepiano. In a process akin to Calvino's novel, the article presents the comings and goings of an exchange process of ideas between the composer and the performer. Physically separated, in Brazil and Portugal, they used video conferences and e-mails to create the work. As the process evolved, technical aspects of the fortepiano and its peculiar sounds were intertwined with adjustments to the composer's creative writing. On the other hand, the combinatorial structure of Calvino's artwork anchored the exchange of musical materials among the work’s movements. This artistic-research project began in April 2014, and led to a recording of Sons Invisíveis (Invisible Sounds), included in the CD Música Nova for Antique Instruments II in 2016. In order to describe this trajectory, this article addresses recent literature in collaboration and performance studies, composition for historical instruments, particularly the fortepiano, the combinatorial nature of Calvino's writing, how the collaborative process was developed, and its final organization, expressing the ineffable character of Calvino's masterpiece through invisible sounds.
Keywords: Artistic Research; Composition; Fortepiano; Invisible Cities